1979
DOI: 10.1002/1097-0142(197911)44:5<1677::aid-cncr2820440522>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Histologic prognostic indicators in hepatocellular carcinoma

Abstract: Survival and histologic features were studied in 80 patients with proven hepatocellular carcinoma (HCC). The overall survival was 50% at 3.5 weeks with a statistically significant drop in mortality rate after 8.5 weeks. Patients with diffuse clear-cell pattern, focal clear-cell pattern, and no clear cells in their tumors had a 50% survival rate at 14 weeks, 6 weeks, and 3 weeks respectively; the differences in survival rates were statistically significant between any pair (p < 0.001). No correlation was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1
1

Year Published

1981
1981
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 5 publications
0
48
1
1
Order By: Relevance
“…Although some researchers claim that their prognosis is similar to that of CHCC or perhaps even worse, 10 more studies have reported PCCCL to have a better prognosis than CHCC. 3,4,7,[11][12][13] Our study confirmed their results and showed significantly higher 1-, 3-and 5-year survival rates in PCCCL patients in univariate analysis. Interestingly, multivariate analysis did not identify the rare histopathologic type of PCCCL as a significant prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Although some researchers claim that their prognosis is similar to that of CHCC or perhaps even worse, 10 more studies have reported PCCCL to have a better prognosis than CHCC. 3,4,7,[11][12][13] Our study confirmed their results and showed significantly higher 1-, 3-and 5-year survival rates in PCCCL patients in univariate analysis. Interestingly, multivariate analysis did not identify the rare histopathologic type of PCCCL as a significant prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical stains are unnecessary when definitive foci of classical trabecular HCC with canaliculi, bile production and Mallory bodies, are present. But in small needle biopsies, or when these features are not present, immunohistochemical stains should be performed to differentiate HCC-CC, which appears to have a better prognosis than nonclear cell HCC, from metastatic clear cell tumors, which are known to have a poor prognosis (21,25). We recommend the Hepatocyte antibody (DAKO) as a screening immunostain in working-up a clear cell tumor in the liver when diagnostic histologic criteria of HCC are absent.…”
Section: Discussionmentioning
confidence: 99%
“…16 Clear cell type HCC also appears to carry a more favorable prognosis 32,33 and have a better responsiveness to hepatic artery chemotherapy than other subtypes of HCC, 34 although there is still controversy in this regard. 35 The incidence of clear cell change did not reach significance between patients from BFD endemic areas and the control areas, implying that arsenic may play a role in the later stages of hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%